(untitled) (REMUNOM, 2025)
This article reviews the bioactive properties of vegetable oil extracted from the Ceru Nut (Goeldinia riparia Huber), belonging to the Lecythidaceae family of the Amazon region. The potential of Ceru Nut oil, which is rich in terpenes, sesquiterpenes, and fatty acids, is discussed, emphasizing its anti-inflammatory, antimicrobial, antifungal, and antioxidant properties. Comparisons with Brazil Nut and Sapucaia Nut oils highlight the protein and energy richness of the Ceru Nut. The methodology involved an exploratory literature review using databases such as Web of Science, SCIELO, PUBMED, and institutional repositories. It concludes that Ceru Nut oil holds significant potential for diverse industrial applications, warranting further research to optimize its sustainable use.